The Promotion and Regulation of Industry in Japan
XIV, 356 p.
Keywords: The international projection of Japan's corporate and technological power is transforming world manufacturing and the international political economy. Debate rages about Japan's economic success and the role of the state in nurturing it. The Japanese background to these debates is widely misunderstood and are analysed in research-based chapters by British and Japanese specialists on government-industry relations. Japanese policies for industrial promotion, regulation and decline are set in a context of comparative political economy. Sectors include pharmaceuticals, shipbuilding and telecommunications in the US and Japan.